1990
DOI: 10.1073/pnas.87.14.5568
|View full text |Cite
|
Sign up to set email alerts
|

Learning causes synaptogenesis, whereas motor activity causes angiogenesis, in cerebellar cortex of adult rats.

Abstract: The role of the cerebellar cortex in motor learning was investigated by comparing the paramedian lobule of adult rats given difficult acrobatic training to that of rats that had been given extensive physical exercise or had been inactive. The paramedian lobule is activated during limb movements used in both acrobatic training and physical exercise. Acrobatic animals had greater numbers ofsynapses per Purkin e cell than animals from the exercise or inactive groups. No significant difference in synapse number or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
633
4
21

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 991 publications
(695 citation statements)
references
References 33 publications
22
633
4
21
Order By: Relevance
“…In cerebellum-related studies, acrobat training (2,19) or an enriched environment (11), but not repeated running, induces synaptogenesis in Purkinje cells. The apparent discrepancy with regard to running-induced synaptogenesis between the present study and previous reports may be explained by the different running intensities and durations employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cerebellum-related studies, acrobat training (2,19) or an enriched environment (11), but not repeated running, induces synaptogenesis in Purkinje cells. The apparent discrepancy with regard to running-induced synaptogenesis between the present study and previous reports may be explained by the different running intensities and durations employed.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies using young rats show that a complex paradigm of "acrobat" training or an enriched environment induces morphological changes in Purkinje cells, while repeated running without skill learning induces angiogenesis in the cerebellum (2,11,19). However, other animal studies reveal that repeated running with defined intensity and duration improves the motor function and prevents the decay of Purkinje cells under various pathological conditions.…”
mentioning
confidence: 99%
“…52,53 Angiogenesis can occur later in life in response to certain physiologic conditions, such as chronic hypoxia, shear stress, exercise, or hormonal fluctuations, thereby altering AVM morphology. [54][55][56][57][58][59] Pathologic conditions such as tumor, stroke, or trauma can also drastically upregulate angiogenesis via VEGF and angiopoietins (Table 2). These factors cause the reactivation of quiescent endothelium, breakdown of vessel walls, and the fusion of perinidal capillaries with the nidus, enlarging the AVM.…”
Section: Angiogenesis In Avms and The Link To Inflammationmentioning
confidence: 99%
“…One cross-sectional study indicated that higher fitness is related to larger frontal and temporal volumes of grey matter (Colcombe et al 2006). Other potential mechanisms may involve more endotheliumdependent vasodilatation as a result of more NO bioavailability (Green et al 2004) and/or cerebral angiogenesis (Rhyu et al 2010;Swain et al 2003;Ding et al 2006;Black et al 1990). In support of this, ageinduced cerebral atrophy appears to be less marked in those with higher aerobic fitness (Colcombe et al 2003).…”
Section: Introductionmentioning
confidence: 99%